2022
DOI: 10.3389/fpsyt.2022.803220
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Prazosin augmentation for treating comorbid treatment-resistant depression and chronic post-traumatic stress disorder

Abstract: Psychological trauma in childhood can lead to post-traumatic disorder (PTSD) with protracted comorbid depression, which responds poorly to conventional antidepressants. Previous studies have shown that prazosin, an α1-adrenergic receptor antagonist, can help eliminate nightmares and improve sleep quality and suicidal ideation in PTSD patients. This case report presents that prazosin had a rapid antidepressant effect in a female adolescent PTSD patient with treatment-resistant depression (TRD). Prazosin improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…In a systematic review of PTSD treatments by Martin et al, prazosin was noted to be first-line recommended treatment for PTSD-related nightmares in two guidelines, while other guidelines recommended it as third-line or provided no guidance at all (11). In addition, the effective dose of prazosin for nightmares tends to vary in case reports from 0.25 mg up to 50 mg daily (12,13). Recommendations based on guidelines suggest that prazosin be started at a low dose and titrated to an effective range of 3-16 mg/night (14); however, long-term efficacy has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of PTSD treatments by Martin et al, prazosin was noted to be first-line recommended treatment for PTSD-related nightmares in two guidelines, while other guidelines recommended it as third-line or provided no guidance at all (11). In addition, the effective dose of prazosin for nightmares tends to vary in case reports from 0.25 mg up to 50 mg daily (12,13). Recommendations based on guidelines suggest that prazosin be started at a low dose and titrated to an effective range of 3-16 mg/night (14); however, long-term efficacy has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiological mechanisms underlying PTSD or trauma-related depression are not known in detail, the efficacy of certain therapies may be indicative of existing pathomechanisms[ 62 ]. For example, in a case study, it was reported that low-dose prazosin led quickly to rapid improvement in depressive symptoms, including cognitive function in a therapy-resistant depressive patient with comorbid chronic PTSD[ 63 ]. The patient had previously received antidepressants that work via serotoninergic, noradrenergic, and dopaminergic mechanisms as well as several sessions of modified electroconvulsive therapy but did not benefit from these treatments, suggesting that prazosin may have acted by different pharmacological mechanisms from monoamine hypothesis[ 64 ].…”
Section: Ptsd and Trauma-related Depressionmentioning
confidence: 99%
“…Альфа1-адреноблокатор празозин с циклом хиназолина в структуре используется при лечении гипертензии, а также посттравматического стрессового расстройства с ночными кошмарами и/или расстройством сна, в том числе в педиатрической практике, оказывая антидепрессивное действие при резистентной к терапии депрессии, устраняя суицидальные мысли [55].…”
Section: влияние на сердечно-сосудистую системуunclassified